Temperature and hospital admissions in the Eastern Mediterranean: a case study in Cyprus - Yichen Wang; Souzana Achilleos; Pascale Salameh; Panayiotis Kouis; Panayiotis K Yiallouros; Elena Critselis; Kleanthis Nicolaides; Filippos Tymvios; Chrysanthos Savvides; Emily Vasiliadou; Stefania I Papatheodorou; Petros Koutrakis; et al. (Environmental Research: Health, 2024)
Exposure to extreme temperatures can trigger a cascade of adverse cardiovascular and respiratory events. However, in Cyprus, a hotspot of climate change in the Eastern Mediterranean region, little is known about the temperature-related cardiorespiratory morbidity risks. We analyzed daily counts of hospital admissions for cardiovascular and respiratory diseases from four general hospitals in three districts in Cyprus from 2000 through 2019. For each district, we fitted time-series quasi-Poisson regression with distributed lag non-linear models to analyze the associations between daily mean temperature (lag 0–21 d) and hospital admissions for cardiorespiratory, cardiovascular, and respiratory diseases. A random-effects meta-analytical model was then applied to pool the district-specific estimates and obtain the national average associations. We analyzed 20 years of cause-specific hospitalization data with a total of 179 988 cardiovascular and respiratory events. The relationships between cardiorespiratory morbidity and temperature were overall U-shaped. During extreme temperature days, 15.85% (95% empirical CI [eCI]: 8.24, 22.40%) excess cardiovascular hospitalizations and 9.59% (95% eCI: −0.66, 18.69%) excess respiratory hospitalizations were attributable to extreme cold days (below the 2.5th percentile). Extreme hot days (above the 97.5th percentile) accounted for 0.17% (95% eCI: 0.03, 0.29%) excess cardiovascular hospitalizations and 0.23% (95% eCI: 0.07, 0.35%) excess respiratory hospitalizations. We found evidence of increased cardiovascular morbidity risk associated with extreme temperatures in Cyprus. Our study highlights the necessity to implement public health interventions and adaptive measures to mitigate the related temperature effects in an understudied region.